Development of Education Accounting Information System - Permatasari, Carolina Lita; Luhsasi, Dwi Iga; Salsabila, Shafira Salwa (Jati: Jurnal Akuntansi Terapan Indonesia, 2024)
The purpose of this research is to develop an education accounting information system and determine the feasibility of using an education accounting information system. This research and development used the ADDIE model. The partner in this research was the OSF Semarang Education Commission Institution. Data collection techniques were carried out using questionnaires, interviews, observations, and documentation. The feasibility results obtained for this education accounting information system include: validation by material experts obtained an assessment of 3.94 with the category ‘Feasible’, validation by media experts obtained an assessment of 4.76 with the category ‘Very Feasible’, and validation by users obtained an assessment of 4.54 with the category ‘Very Feasible’. Based on the validation results, it can be concluded that the education accounting information system is very feasible to be implemented at the OSF Semarang Education Commission Institution so that it can facilitate the work of the Institution Management and College Management in preparing financial reports. The implications of this research include improving the efficiency and accuracy of institutional financial management through technology, providing guidelines for transparency and accountability, and improving the quality of education and public trust in budget management.